MeV-range velocity-space tomography from gamma-ray and neutron emission spectrometry measurements at JET. (14th March 2017) - Salewski, M.; Nocente, M.; Jacobsen, A.S.; Binda, F.; Cazzaniga, C.; Ericsson, G.; Eriksson, J.; Gorini, G.; Hellesen, C.; Hjalmarsson, A.; Kiptily, V.G.; Koskela, T.; et al.
Abstract: We demonstrate the measurement of a 2D MeV-range ion velocity distribution function by velocity-space tomography at JET. Deuterium ions were accelerated into the MeV-range by third harmonic ion cyclotron resonance heating. We made measurements with three neutron emission spectrometers and a high-resolution γ -ray spectrometer detecting the γ -rays released in two reactions. The tomographic inversion based on these five spectra is in excellent agreement with numerical simulations with the ASCOT–RFOF and the SPOT–RFOF codes. The length of the measured fast-ion tail corroborates the prediction that very few particles are accelerated above 2 MeV due to the weak wave-particle interaction at higher energies.